Integrating African perspectives into the Global Goal on Adaptation (GGA) indicators - Nzuki, Esther Ndumi; Njuguna, Lucy Wanjiku (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The Eastern Africa Farmers Federation (EAFF) collaborated with Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) to host a workshop aimed at ensuring farmers' voices are included in indicators for the Global Goal on Adaptation (GGA).